The Tensions of Belonging - Chiara Invernizzi (Balthazar)
This article examines the tension between political obligation and personal loyalty in the context of exile, drawing on the theories of Judith Shklar and utilizing Hisham Matar’s literary work, My Friends (2023), as a primary analytical framework. Through an interdisciplinary investigation that interweaves political philosophy, history, and literature, the work examines how exile compels individuals to confront complex moral dilemmas, thereby questioning their relationships with the state, the community, and themselves. The examples presented in the essay provide a contemporary, narrative perspective on the fragmented identity of exile.